Establishment of in vitro Calibration Curve for 60Co-γ-rays Induced Phospho-53BP1 Foci, Rapid Biodosimetry and Initial Triage, and Comparative Evaluations With γH2AX and Cytogenetic Assays - Chaurasia, Rajesh Kumar; Shirsath, Kapil B.; Desai, Utkarsha N.; Bhat, Nagesh N.; Sapra, B. K. (Frontiers in Public Health, 2022)
A rapid and reliable method for biodosimetry of populations exposed to ionising radiation in the event of an incident or accident is crucial for initial triage and medical attention/management. DNA-Double Strand Breaks (DSBs) are known to be radiation specific and DSB-repair proteins (53BP1, gamma H2AX, ATM, etc) are considered as promising markers of DSB quantification. Immunofluorescence technique serves as a sensitive and reproducible tool for the detection and quantification of these DSB-repair proteins which can be used for biological dose estimations. In this study, Dose Response Curves (DRCs) were generated for 60Co-gamma-rays induced phosphorylation of 53 Binding Protein 1 (53BP1) at 1, 2, 4, 8, 16 and 24 h, post irradiation, for dose range 0.05 - 4 Gy, using fluorescence microscopy. Following ISO recommendations, Minimum Detection Limits (MDLs) were estimated to be 16, 18, 25, 40, 50 and 75 mGy for DRCs generated at 1, 2, 4, 8, 16 and 24 h, post irradiation. Colocalization and correlation of phosphorylated 53BP1 and gamma H2AX was also illustrated in irradiated lymphocytes, to gain dual conformation. Multiparametric validation of the established curve was made by gamma H2AX-immunofluorescence, Dicentric Chromosomal Aberration (DCA) and Reciprocal Chromosomal Translocations (RCT) assays, through 6 dose blinded samples. Respective, in house established DRCs were employed to reconstruct the doses. Estimated doses were found to be within the variation of 4.1 - 24 %. For lower doses (0.05 - 2 Gy), immunofluorescence assays (53BP1 and gamma H2AX) gave closer estimates (variation, - 4.1 to + 9 %) in comparison to cytogenetic assays (variation, - 8.5 to 24 %) and for higher doses (3 and 4 Gy) cytogenetic and immunofluorescence, both the assays gave comparable close estimates, with - 11.3 to + 14.3 % and - 10.3 to - 13.7 %, variations, respectively.